2016
DOI: 10.1177/1528083715594977
|View full text |Cite
|
Sign up to set email alerts
|

Thermal protection retention of fire protective clothing after repeated flash fire exposure

Abstract: Fire protective clothing worn by the emergency responders may be exposed to intensive heat condition time and time again during a firefighting work. In this research, the level of thermal protection retained by the fire protective clothing after repeated exposures to flash fire was investigated from bench-scale test to full-scale test. A thermal protective performance tester and an instrumented manikin with a transverse motion system device which was capable of simulating the action of running across the flame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In the future, thermal protective performance could be evaluated in consideration with the attenuation factors and empirical models could be developed for properly predicting the thermal protective performance of fabrics. Moreover, Wang and Li (2015) [73] found that repeated flame exposure to fabric samples continuously reduce the thermal protective performance of the fabrics depending upon the polymeric fibers used in the fabrics. This thermal protective performance also was significantly affected by the shrinkage of the fabrics under flame exposure [74].…”
Section: Thermal Protective Performance Under Flame Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…In the future, thermal protective performance could be evaluated in consideration with the attenuation factors and empirical models could be developed for properly predicting the thermal protective performance of fabrics. Moreover, Wang and Li (2015) [73] found that repeated flame exposure to fabric samples continuously reduce the thermal protective performance of the fabrics depending upon the polymeric fibers used in the fabrics. This thermal protective performance also was significantly affected by the shrinkage of the fabrics under flame exposure [74].…”
Section: Thermal Protective Performance Under Flame Exposurementioning
confidence: 99%
“…Wang and Li (2016) [73] Repeated flame exposure could reduce the thermal protective performance depending on the types of fibers used in the fabrics.…”
Section: Author Findingsmentioning
confidence: 99%
“…Research based on full-scale manikin tests revealed that garment shrinkage during exposure could greatly reduce the air gap and potentially cause a significant decrease in the performance of thermal-protective clothing [33,43]. Surface area changes could represent the thermal shrinkage of the fire-retardant fabrics [44]. A higher surface area retention indicated better thermal stability of the fabrics.…”
Section: Discussionmentioning
confidence: 99%
“…The air possess good thermal insulator as it's material thermal conductivity is less than the fabrics [16]. The air gap can significantly improve as the air gap reached 6.4mm thickness between fabric and the sensor [17]. The air gap thickness that located between the fabric and skin layer the thickness varies at each of body location [15].…”
Section: Introductionmentioning
confidence: 99%